2013
DOI: 10.11114/jets.v1i1.24
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Beliefs on Student Competence in Mathematical Modeling – An Intervention Study

Abstract: This paper presents an intervention study whose aim was to promote teacher beliefs about mathematics and learning mathematics and student competences in mathematical modeling. In the intervention, teachers received written curriculum materials about mathematical modeling. The concept underlying the materials was based on constructivist ideas and findings from mathematics education. Teacher beliefs about mathematics, learning and self-efficacy were expected to have a major impact on their classroom practices. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, the findings of these studies also indicate that teaching and learning are determined also by a range of other factors in addition to instructional materials. For example, Mischo and Maass (2013) address factors such as teachers' beliefs and personal backgrounds, and their professional development experiences while Ball et al (2008) and Jackson, Wilhem, and Munter (2018) clarify the relations between teachers' knowledge and perspective, and their classroom practices. Andrews (2013), for his part, identifies national and cultural factors that frame didactic strategies and learning goals in mathematics teaching across four European countries.…”
Section: Strategies For Implementing Instructional Improvement At Scalementioning
confidence: 99%
“…However, the findings of these studies also indicate that teaching and learning are determined also by a range of other factors in addition to instructional materials. For example, Mischo and Maass (2013) address factors such as teachers' beliefs and personal backgrounds, and their professional development experiences while Ball et al (2008) and Jackson, Wilhem, and Munter (2018) clarify the relations between teachers' knowledge and perspective, and their classroom practices. Andrews (2013), for his part, identifies national and cultural factors that frame didactic strategies and learning goals in mathematics teaching across four European countries.…”
Section: Strategies For Implementing Instructional Improvement At Scalementioning
confidence: 99%
“…Mathematical modelling is defined as solving real-world problems with the help of mathematics (Mischo & Maaß, 2013). Modelling activities involve partial, ambiguous or undefined information about a situation (English & Fox, 2005).…”
Section: Theoretical Background Modellingmentioning
confidence: 99%
“…In addition to these factors, we later questioned how teacher beliefs could affect how students benefit from these lessons. It has been shown that teacher beliefs on what is required to be successful in a particular subject area can have a large impact on students' self efficacy and performance [3][4][5][6]. This extends to teacher's beliefs on multicultural issues as well [7].…”
Section: Introductionmentioning
confidence: 99%